2003
DOI: 10.1254/fpj.122.515
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the study of AMPA receptors.

Abstract: As glutamate is a dominant excitatory neurotransmitter in the central nervous system, glutamate receptors, and especially AMPA receptors, are located ubiquitously in all brain areas. In this paper, we reviewed recent advances of studies on AMPA receptor functions. AMPA receptors are cation-conducting complexes composed of various combinations of four subunits (GluR1 to GluR4). The glutamine residue located in the pore-forming segment of GluR2 subunit (Q/R site) is changed to arginine by RNA editing at the pre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Recently, we demonstrated that a significant proportion of GluR2 mRNA was unedited at the Q/R site in spinal motor neurons of postmortem patients with sporadic ALS. This is in marked contrast to the fact that all GluR2 mRNA was edited in the motor neurons of control subjects (Takuma et al, 1999;Kawahara et al, 2004) and of patients with motor neuron diseases other than sporadic ALS (Kawahara et al, 2006), as well as in dying neurons in other neurodegenerative diseases, including Purkinje cells of patients with spinocerebellar degeneration (Paschen et al, 1994;Akbarian et al, 1995;Kawahara et al, 2004;Suzuki et al, 2003). The disease specificity of inefficient GluR2 Q/R site editing implies the pathogenic relevance of ADAR2 insufficiency in the death of motor neurons in sporadic ALS but leaves open the possibility that other genes whose products remain unedited by ADAR2 insufficiency might contribute to the demise of motor neurons.…”
Section: Introductionmentioning
confidence: 82%
“…Recently, we demonstrated that a significant proportion of GluR2 mRNA was unedited at the Q/R site in spinal motor neurons of postmortem patients with sporadic ALS. This is in marked contrast to the fact that all GluR2 mRNA was edited in the motor neurons of control subjects (Takuma et al, 1999;Kawahara et al, 2004) and of patients with motor neuron diseases other than sporadic ALS (Kawahara et al, 2006), as well as in dying neurons in other neurodegenerative diseases, including Purkinje cells of patients with spinocerebellar degeneration (Paschen et al, 1994;Akbarian et al, 1995;Kawahara et al, 2004;Suzuki et al, 2003). The disease specificity of inefficient GluR2 Q/R site editing implies the pathogenic relevance of ADAR2 insufficiency in the death of motor neurons in sporadic ALS but leaves open the possibility that other genes whose products remain unedited by ADAR2 insufficiency might contribute to the demise of motor neurons.…”
Section: Introductionmentioning
confidence: 82%
“…This is in marked contrast to the fact that all GluA2 mRNA was edited in the motor neurons of control subjects (Takuma et al, 1999; Kawahara et al, 2004), in patients with motor neuron diseases other than sporadic ALS (Kawahara et al, 2006), and in dying neurons in other neurodegenerative diseases, including the Purkinje cells of patients with spinocerebellar degeneration (Paschen et al, 1994; Akbarian et al, 1995; Suzuki et al, 2003; Kawahara et al, 2004). The high disease specificity warrants an investigation of how inefficient GluA2 RNA editing leads to neuronal death.…”
Section: Introductionmentioning
confidence: 92%
“…AMPA receptors are cation-selective tetrameric heterooligomers formed by combinations of the subunits GluR1, GluR2, GluR3, and GluR4 (Hollmann et al 1989;Boulter et al 1990; Keinanen et al 1990; Wisden and Seeburg 1993;Sommer and Seeburg 1992;Fletcher and Lodge 1996;Quirk and Nisenbaum 2002;Suzuki et al 2003;Brorson et al 2004). These subunits are of about 900 amino acids and contain a large extracellular N-terminal domain.…”
Section: Structure and Cns Distribution Of Ampa Receptorsmentioning
confidence: 99%